КОМПЕТЕНТНА СОЦІАЛІЗАЦІЯ УЧНІВ ЗАГАЛЬНООСВІТНІХ Ш КІЛ-ІНТЕРНАТ ІВ ЗАСОБАМИ ОРГАНІЗАЦІЇ ЇХ БЕЗПЕЧНОЇ ЖИТТЄДІЯЛЬНОСТІ (Педагогіка вищої та середньої школи, 2008)
In this article basic approaches are resulted in organization of safe vital functions of students of schools-boarding-schools for their future successful socialization and the basic requirements are presented to the schoolboys of these establishments which must be produced them during competent organization of vital functions in modem society.